Immunogenicity and safety of a 12-valent pneumococcal conjugate vaccine in infants aged 6-10 weeks: a randomized double-blind active-controlled trial - Jonghoon Shin; Jamaree Teeratakulpisarn; Thanyawee Puthanakit; Tuangtip Theerawit; Ji Hwa Ryu; Jinhwan Shin; Seulgi Lee; Hayoung Lee; Kyungjun An; Hun Kim (The Korean Pediatric Society, 2020)
Background Pneumococcal diseases among children aged <5 years worldwide are associated with high annual mortality rates. Purpose This study aimed to evaluate the immunogenicity and safety of GBP411, a 12-valent pneumococcal conjugant vaccine, with a dosing schedule of 2 primary doses plus 1 booster dose (2p+1) in healthy infants. Methods This randomized active-controlled (Prevnar 13) double-blind phase 2 trial enrolled healthy subjects aged 6-10 weeks. Three serum concentrations of pneumococcal serotype-specific immunoglobulin G (IgG) were evaluated using the pneumococcal serotype-specific pneumonia polysaccharide enzyme-linked immunosorbent assay at 1 month after the primary doses and before and 1 month after the booster dose. The pneumococcal serotype-specific IgG titer was evaluated using a multiplex opsonophagocytic assay in a subset of 15 subjects per group. Results After administration of the primary doses, the proportion of subjects who achieved pneumococcal serotype-specific IgG concentrations of >0.35 μg/mL was lower for some serotypes in the GBP411 group than in the comparator group (6B: 20.83% vs. 39.22%, P=0.047 and 19A: 58.33% vs. 90.20%, P<0.001). However, after administration of the booster dose, >97% of the subjects in each group achieved IgG concentrations of ≥0.35 μg/mL for all 12 serotypes. Increased immunogenicity was observed for some serotypes that showed significant intergroup differences after administration of the primary doses but not after the booster dose. We also found no significant intergroup difference in the overall incidence of solicited local adverse events. Furthermore, the overall incidence of solicited systemic adverse events was significantly lower in the GBP411 group than in the comparator vaccine group (79.59% vs. 98.04%; P=0.003). Conclusion The GBP411 vaccine with a dosing schedule of 2p+1 may be immunogenic and safe for healthy infants.